The Personal Archive of Martin Ludwig Rhesa: A Reconstruction - Aleknavičienė, Ona (Knygotyra, 2020)
This article deals with materials and data on the manuscripts that were present in the personal archive of Martin Ludwig Rhesa (or Ludwig Jedemin Rhesa, 1776–1840) – professor at the University of Königsberg, scholar of folklore, editor and researcher of the Bible, Church historian, publisher of Kristijonas Donelaitis’s “Metai” and his fables. These manuscripts are traditionally referred to in Lithuanian literary historiography as the Rhesa Archive. The history of the manuscripts’ preservation after 1840 is described: relocation to the Royal Secret Archive in Königsberg, the placing of a part of the archive in the State Archive of Gdańsk in 1903, and its appearance in Lithuanian libraries after the Second World War. The principal aim of this study is to determine the manuscripts that had belonged to Rhesa’s personal archive in the 19th c., i.e., to reconstruct his previous archive. It is sought to determine the current location where it is being kept (the library or fund). In evaluating Rhesa’s attempts to collect sources on the Lithuanian language, literature, history, and folklore, the scholarly and cultural interests that these writings attest to are demonstrated.